Sovremennoe sostojanie i napravlenija razvitija rossijskich legkoatleticeskich pryžkov - Ogandzhanov, A. L.; Kosikhin, V. P.; Tsyplenkova, E. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The current research is focused on the analysis of problems and "pressure points" that athletic jumping is faced up to. The dynamics of main indicators in various jumping disciplines and trends in Worldwide and Russian athletics are studied nowadays. These reasons are based on a comparison of the main indicators of competitive activity of world elite jumpers and the strongest Russian jumpers. A research of the run-up phase in these jumping disciplines was carried out. Some directions for improving the training of Russian athletes-jumpers for the near future were identified.